Inovasi Teknologi Panel Surya untuk Meningkatkan Produktivitas Pertanian di Desa Lempangang - Muhammad Akil; Andi Baso Kaswar; Andi Alamsyah Rivai (Jurnal Pemberdayaan Masyarakat, 2024)
This community service program aims to increase agricultural productivity and improve the welfare of the "Sejahtera" Farmer Group in Lempangang Village, Bajeng Subdistrict, Gowa Regency, through the implementation of solar-powered irrigation technology. The project focuses on replacing traditional diesel-fueled water pumps with more environmentally friendly and cost-effective solar-powered pumps. Furthermore, the introduction of smart farming technologies utilizing IoT devices powered by solar energy provides farmers with timely information on soil fertilization and climate changes, thus improving their adaptability to climate challenges. The project also includes the construction of solar panel frames, the installation of controllers, and solar panels in the farmers' rice fields, where the technology is already in use. Initial tests on solar panels, controllers, and water pumps demonstrated the efficiency of the system in supporting irrigation needs. Through this project, we aim to establish a model for sustainable agricultural practices that not only reduce the environmental impact but also enhance the economic conditions of farmers in the region. The outcomes of this initiative include increased productivity, reduced operational costs, and the empowerment of farmers through the application of innovative, renewable energy technologies in agriculture.